About “russicisms” of Berlinski Sbornik - Stankov, Rostislav (Studia Ceranea, 2015)
The article deals with the problem of the so-called “eastslavonic influence” on southslavonic literature in 12th–13th centuries. The idea, based on claims that some Bulgarian and Serbian manuscripts of the period (among them Berlinski Sbornik) contain russicisms, is complete misconception.